FRI0044 Early treatment with dmards improves radiological outcome in patients with rheumatoid arthritis. (1st June 2001) - Allaart, CF; Wieringa, JW; Huizinga, TW; Breedveld, FC
Abstract : Background: For years, patients with rheumatoid arthritis were treated with DMARDs only if they showed severe disease progression with insufficient relieve with NSAIDs. Anti-malarials were prescribed more often than methotrexate and sulphasalazin. However, since side effects of DMARDs and NSAIDs have been shown to be similar, and because it is apparent that radiological damage occurs early in the course of rheumatoid arthritis, rheumatologists have gradually become more aggressive in the treatment of RA: DMARDs, especially methrotrexate and sulphasalazin, are prescribed earlier and in higher dosages, sometimes also in combinations. Do the patients benefit from this change in attitude? Objectives: Methods: Since 1993 patients with recent onset arthritis are seen and followed up in our Early Arthritis Clinic. In a retrospective study of all patients who were diagnosed in 1994 (n = 28) and 1998 (n = 52) with RA and probable RA (1 in 1994, 2 in 1998), we evaluated the erosion progression (Sharp/van der Heijde method) between the time of presentation and 2 years later. Results: in 1994, 28 patients and in 1998, 52 patients were diagnosed with RA or probable RA (n = 1, n = 2, resp.). At presentation, there were no differences in sex distribution, mean age, duration of symptoms, number of inflamed joints, mean ESR, percentage positive for Rheumatoid Factor-IgG, or Sharp/van der Heijde score. Mean duration after presentation before a DMARD was started in 1994 was 7.9 months, in 1998 1, 8 months. After 2 years follow-up, 36% of patients included in 1994 were still without DMARD-treatment, and of 36% who started on antimalarials, 60% were still on those drugs. Of the patients included in 1998, 4% had received no DMARDs in the next 2 years, and 63% resp. 13% received sulphasalazin resp. methotrexate as first drug. Of the 20% who started on antimalarials, 60% had discontinued and started another DMARD after on average 6 months. The average progression of the Sharp/van der Heijde score was 36.5 for the patients included in 1994, and 9.5 for those included in 1998. Conclusion: Changes in perception of how to treat RA, inspired by less fear for side effects of DMARDs and awareness of early joint destruction, have resulted in less erosion progression in the patients.